Molecular Mechanisms of Hypoxic-Ischemic Encephalopathy in Newborn Piglets - Varga Viktória Éva; Domoki Ferenc (2018)
Perinatal asphyxia (PA) is among the most common causes of neonatal deaths. In the survivors, PA may result in multi-organ damage including hypoxic-ischemic encephalopathy (HIE) that often leads to life long disabilities. Understanding the pathophysiological mechanisms of HIE is key to the development of neuroprotective therapies, and large animal PA/HIE models can help to bridge the translational gap between studies at the molecular/cellular level and the cotside management. Our research group has previously shown that 8- or 20-min-long PA resulted in incrementally severe HIE in newborn pigs and that neuronal-vascular injury was alleviated by molecular H2 ventilation in these models. Our purpose was to address several hypotheses related to the mechanisms of neuronal injury as well as H2 induced neuroprotection using brain samples chiefly obtained from these previous studies. First, we investigated the abundance of cyclooxygenase-2 (COX-2) immunopositive neurons in our samples, as COX-2 is known to be an important source of reactive oxygen species in the neonatal brain, however, induction of neuronal COX-2 by PA has not yet been shown in piglets. Oxidative cellular (DNA) damage was visualized with 8-hydroxy-deoxyguanozin immunohistochemistry and was correlated with neuronal COX-2 expression. Second, microglia were visualized with Iba-1 immunohistochemistry in order to detect PA induced neuroinflammatory changes in microglial morphology quantified by the so called ramification index. Third, the ratio of active (phosphorylated) and total forms of ERK and Akt kinases were determined using Western blots to assess the activity and PA induced changes of these important antiapoptotic signal transduction mechanisms. PA increased neuronal COX-2 expression neurons in several brain regions, where high percentage of COX-2 positive neurons always coincided with severe neuronal damage. In the parietal cortex, neuronal COX-2 abundance correlated both with oxidative damage and microglial activations.H2 attenuated all of these PA induced changes. Erk and Akt displayed high degree of phosphorylation in controls that was unaffected by PA in any studied region. In conclusion, PA-induced neuronal COX-2 induction, oxidative damage and neuroinflammation all contribute to neuronal injury and are reduced by H2, however, induction of antiapoptotic pathways appear to have a minor neuroprotective capacity in our HIE model.
Disszertacio
Keywords: elméleti orvostudományok